2016
DOI: 10.1007/s11420-016-9533-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Revision Rates of Non-modular Constrained Versus Posterior Stabilized Total Knee Arthroplasty: a Propensity Score Matched Cohort Study

Abstract: Background: Attaining stability during total knee arthroplasty (TKA) is essential for a successful outcome. Although traditional constrained total knee prostheses have generally been used in conjunction with intramedullary stems, some devices have been widely used without the use of stems, referred to as non-modular constrained condylar total knee arthroplasty (NMCCK). Questions/Purposes: The aim of this study was to compare revisions rates after total knee replacement with a non-modular constrained condylar t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…This may be due to those patients with CCK implants having poor bone stock, ligamentous deficiency, or large preoperative deformities. A large proportion of the CCK TKAs that failed in our series was a specific non-modular CCK without stem extensions that may be predisposed to aseptic loosening of the femoral component [19]. Previous literature provided evidence that use of a second generation CCK implant in primary TKA is safe in the short to medium follow up period [20][21] [22], but contradictory reports exist that in long-term follow up, CCK implants have higher complication rates and decreased survival compared to standard TKAs, but again the majority of patients with a CCK primary TKA implant may have severe deformity or instability pre-operatively [23].…”
Section: Discussionmentioning
confidence: 89%
“…This may be due to those patients with CCK implants having poor bone stock, ligamentous deficiency, or large preoperative deformities. A large proportion of the CCK TKAs that failed in our series was a specific non-modular CCK without stem extensions that may be predisposed to aseptic loosening of the femoral component [19]. Previous literature provided evidence that use of a second generation CCK implant in primary TKA is safe in the short to medium follow up period [20][21] [22], but contradictory reports exist that in long-term follow up, CCK implants have higher complication rates and decreased survival compared to standard TKAs, but again the majority of patients with a CCK primary TKA implant may have severe deformity or instability pre-operatively [23].…”
Section: Discussionmentioning
confidence: 89%
“…There is no need to recut the femur or use stems because of a common femoral box cut across different levels of constraint, which may be used without femoral or tibial stems. 6 , 21 Moussa et al 22 reported that there is an increased revision rate in a stemless constrained condylar prosthesis compared with a PS prosthesis. The basic tenets of careful soft-tissue balancing for stable total knee arthroplasty with equal flexion and extension gaps still hold true; however, a case can be made for the routine use of a more constrained prosthesis, such as a CCK prosthesis, prophylactically.…”
Section: Discussionmentioning
confidence: 99%
“…14,35,37 However, some studies have cautioned against higher aseptic loosening rates in the use of similar stemless VVC knee implants in the primary setting. [41][42][43] The findings of these studies, however, should be interpreted with caution as they have the same VVC implant design in common. The predominant cause of failure in these studies was femoral component loosening.…”
Section: Discussionmentioning
confidence: 90%